2016
DOI: 10.17795/modernc.8857
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Quercetin Topical Cream on Phlebitis Caused by Peripheral Intravenous Catheters: A Randomized Controlled Trial

Abstract: Background: Phlebitis is among the most common complications of intravenous therapy. It significantly correlates with the length of hospital stay and mortality rate. Objectives: This study sought to examine the effects of quercetin topical cream on phlebitis caused by peripheral intravenous catheters. Methods: This single-blind randomized controlled trial was done in 2015 on 66 patients hospitalized at the internal medicine ward of Valiasr (PBUH) hospital, Birjand, Iran. The patients were conveniently recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Application of the ointment‐based treatment was by massage and dressing. The calendula was applied by massage 3 times a day for 3 days (Jourabloo et al, 2017), the aloe vera with a gauze dressing twice a day for 2 days (Vidhya, 2017) and the quercetin with a sterile dressing twice a day for 3 days (Ghorbani et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Application of the ointment‐based treatment was by massage and dressing. The calendula was applied by massage 3 times a day for 3 days (Jourabloo et al, 2017), the aloe vera with a gauze dressing twice a day for 2 days (Vidhya, 2017) and the quercetin with a sterile dressing twice a day for 3 days (Ghorbani et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…50% present a low risk of bias in the generation of random sequences, though it should be noted that 12 of the included studies were quasi‐RCT and 2 pre‐experimental. Allocation concealment (selection bias) only took place in three of the studies (Bigdeli Shamloo et al, 2019; Ghorbani et al, 2016; Selva Grace et al, 2020). A similar situation of uncertainty is found in the blinding of participants and personnel (performance bias), which is only described in 4 of the studies (Basu et al, 2017; Ghorbani et al, 2016; Selva Grace et al, 2020; Sharma, 2016), and in the blinding of results assessment (detection bias), which is reported in just 3 studies (Basu et al, 2017; Bigdeli Shamloo et al, 2019; Selva Grace et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghorbani et al . [ 44 ] also reported that 2% quercetin cream was effective in treating phlebitis. Flavonoid helps in increasing collagen synthesis, promotes cross-linking of collagen, decreases the degradation of soluble collagen, promotes conversion of soluble collagen to insoluble collagen, and hinders the catabolism of soluble collagen.…”
Section: Discussionmentioning
confidence: 99%